2018
DOI: 10.1097/aln.0000000000002253
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Decline after Delirium in Patients Undergoing Cardiac Surgery

Abstract: What We Already Know about This Topic What This Article Tells Us That Is New Background Delirium is common after cardiac surgery and has been associated with morbidity, mortality, and cognitive decline. However, there are conflicting reports on the magnitude, trajectory, and domains of cognitive change that might be affected. The authors hypothesized that patients with delirium would experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
108
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 56 publications
(68 reference statements)
7
108
1
1
Order By: Relevance
“…POD has been associated with decline in cognitive performance in the weeks to months after surgery in several welldone studies. 6,8,40,161,162 One year after surgery, there is often recovery in cognitive function. However, many patients with delirium do not recover to baseline cognitive status, although there is some disagreement between studies.…”
Section: Prognosis and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…POD has been associated with decline in cognitive performance in the weeks to months after surgery in several welldone studies. 6,8,40,161,162 One year after surgery, there is often recovery in cognitive function. However, many patients with delirium do not recover to baseline cognitive status, although there is some disagreement between studies.…”
Section: Prognosis and Outcomesmentioning
confidence: 99%
“…However, many patients with delirium do not recover to baseline cognitive status, although there is some disagreement between studies. 6,8,40,161,162 Few prospective studies have examined cognitive outcomes beyond 1 yr, but the largest study of patients undergoing noncardiac surgery found greater cognitive decline beginning at 2 yr after surgery in patients with delirium compared with patients who did not develop delirium. 6 This same group found that patients with the highest delirium severity had the fastest rate of decline, with a doseeresponse relationship between delirium severity and long-term cognitive decline.…”
Section: Prognosis and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…are common in patients who undergo cardiac surgery with cardiopulmonary bypass. 1 There is an ongoing debate regarding the neurocognitive benefits of off-pump coronary artery bypass grafting (OPCAB) relative to on-pump procedures. A proposed theory with the use of OPCAB is the reduced neuroinflammatory response.…”
Section: Delirium and Postoperative Cognitive Dysfunction (Pocd)mentioning
confidence: 99%
“…Data suggested that patients with POD are at higher risk of developing a decline in cognitive performance than those without POD, but this relationship only applies to the first months after surgery and not in the long term [ 25 ]. Nevertheless, POD may be treated as an independent risk factor of postoperative cognitive dysfunction [ 26 ]. In cardiac surgery, the problem of postoperative delirium usually appears within the first five days after the procedure, and many other confounding factors need to be excluded [ 27 , 28 ].…”
Section: Delirium After Cardiac Surgery and Risk Factorsmentioning
confidence: 99%